2022
DOI: 10.3390/ijerph19148671
|View full text |Cite
|
Sign up to set email alerts
|

“I Think That’s the Most Beneficial Change That WIC Has Made in a Really Long Time”: Perceptions and Awareness of an Increase in the WIC Cash Value Benefit

Abstract: During the COVID-19 pandemic, the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) Cash Value Benefit (CVB) for fruits and vegetables increased by roughly USD 25/month/person. We sought to understand WIC participant perceptions of this change and barriers and facilitators to using the CVB. We conducted 10 virtual focus groups (5 rural, 5 urban/suburban) with WIC participants (n = 55) in North Carolina in March 2022. Focus groups were recorded and transcribed. We open-coded the cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 63 publications
5
16
0
Order By: Relevance
“…Duffy et al (2022) [ 74 ] explored awareness, barriers and facilitators, and perceived impact of the higher allotment for FVs among WIC participants in North Carolina. Martinez et al (2022) [ 75 ] explored satisfaction and use of the higher FV allotment among WIC participants in southern California.…”
Section: Special Issue Contributions To Advancing Nutrition Security ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Duffy et al (2022) [ 74 ] explored awareness, barriers and facilitators, and perceived impact of the higher allotment for FVs among WIC participants in North Carolina. Martinez et al (2022) [ 75 ] explored satisfaction and use of the higher FV allotment among WIC participants in southern California.…”
Section: Special Issue Contributions To Advancing Nutrition Security ...mentioning
confidence: 99%
“…Martinez et al (2022) [ 75 ] explored satisfaction and use of the higher FV allotment among WIC participants in southern California. Results from both studies indicated WIC participants believed the prior allotment for FVs was too low to support accessing adequate variety and quality of FVs [ 74 , 75 ]. Martinez and colleagues also find evidence that the increased FV allotment not only favorability impacted WIC participants, but also improved FV accessibility/consumption for other household members [ 75 ].…”
Section: Special Issue Contributions To Advancing Nutrition Security ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies in California [ 25 , 26 ], North Carolina [ 27 ], and Delaware [ 28 ] suggest that this temporary increase is highly valued by WIC caregivers and may be linked with improvements in FV affordability, purchasing, and consumption, as well as overall WIC satisfaction. However, research on the perceived impact of this emergent temporary increase remains limited to mostly qualitative studies [ 25 , 27 , 28 ]. It is also unclear whether any potential benefits or impacts of the CVB increase may have been mitigated by structural inequities in access to FV.…”
Section: Introductionmentioning
confidence: 99%